HUBUNGAN PENGETAHUAN DAN SIKAP KELUARGA DENGAN PERILAKU PENCEGAHAN FILARIASIS DI DESA KASANG LOPAK ALAI KECAMATAN KUMPEH ULU KABUPATEN MUARO JAMBI - ., Monalisa (JURNAL HEALTH AND SPORT, 2013)
Prevention in health is defined as the science and art of preventing disease, and prolonging life and improving physical and mental health of efficiency for various community groups for health workers, family doctors through a process of individual and community activities one of which is the prevention of filariasis. This study aims to determine the relationship of knowledge and attitudes of families with filariasis prevention behaviors. This research is quantitative cross-sectional design. Population of 456 with a sample of 87 respondents using proportional random sampling technique.. Instrument used questionnaires. Data that has been tested for validity and reabiliti analyzed using univariate and bivariate chi-square test. Research findings show that of the 87 respondents, 47 (54%) had poor behavior toward prevention of filariasis and 40 (46%) had good behavior, 45 (51.7%) had a low level of knowledge and 42 (48.3% ) has a high level of knowledge, 38 (43.7%) had a poor attitude and 49 (56.3%) had a good attitude. Statistical test results obtained knowledge that there is a relationship (p-value =008) and family attitudes (p-value = 0.010) with filariasis prevention behaviors. Nurses are expected to improve their counseling, both individually and collectively to the public and researchers to come. For further research are expected to conduct research about lifestyle and environment that may affect the incidence of filariasis.